A Comparative Study of Scripted versus Unscripted Morning Reports: Results from a Prospective Multicenter Study. Issue 7 (July 2022) - Jagannath, Anand D.; Kwan, Brian; Heppe, Daniel B.; Beard, Albertine S.; Cornia, Paul B.; Albert, Tyler; Lankarani-Fard, Azadeh; Bradley, Joel M.; Guidry, Michelle M.; Tuck, Matthew; Fletcher, Kathlyn E.; Gunderson, Craig G.
Abstract : Morning report is one of the central activities of internal medicine residency education. The most common formats of morning reports are scripted reports (prepared in advance with planned didactics) and unscripted reports (delivered without planned didactics). The process and content of these report formats have not been previously compared, however. The authors prospectively observed 198 case-based morning reports at 10 Veterans Affairs academic medical centers across the United States to characterize the differences between scripted and unscripted morning reports. Abstract: Objectives: Morning report is one of the central activities of internal medicine residency education. The two most common morning report formats are scripted reports, which use preselected cases with prepared didactics, and unscripted reports in which a case is discussed without preparation. No previous study has compared these two formats. Methods: We conducted a prospective observational study of morning report conducted at 10 academic medical centers across the United States. Results: A total of 198 case-based morning reports were observed. Of these, 169 (85%) were scripted and 29 (15%) were unscripted. Scripted reports were more likely to present a case with a known final diagnosis (89% vs 76%, P = 0.04), use electronic slides (76% vs 52%, P = 0.01), involve more than 15 slides (55% vs 3%, P < 0.001), and reference the medical literature (61% vs 34%, P = 0.02), including professional guidelines (32% vs 10%, P = 0.02) and original research (25% vs 0%, P = 0.001). Scripted reports also consumed more time in prepared didactics (8.0 vs 0 minutes, P < 0.001). Unscripted reports consumed more time in case history (10.0 vs 7.0 minutes, P < 0.001), physical examination (3.0 vs 2.0 minutes, P = 0.06), and differential diagnosis (10.0 vs 7.0 minutes, P = 0.01). Conclusions: Most contemporary morning reports are scripted. Compared with traditional unscripted reports, scripted reports are more likely to involve a case with a known diagnosis, use extensive electronic presentation slides, and consume more time in didactics, while unscripted reports consume more time in the early diagnostic process, including history, physical examination, and differential diagnosis. Residency programs interested in emphasizing these aspects of medical education should encourage unscripted morning reports.